Adolescent Alcohol Exposure Increases Orexin-A/Hypocretin-1 in the Anterior Hypothalamus - Amodeo, Leslie R. (Alcohol, 2020)
Adolescence is a time of marked changes in sleep, neuromaturation, and alcohol use. While there is substantial evidence that alcohol disrupts sleep and that disrupted sleep may play a role in the development of alcohol use disorders (AUD), there is very little known about the brain mechanisms underlying this phenomenon. The orexin (also known as hypocretin) system is fundamental for a number of homeostatic mechanisms including the initiation and maintenance of wakefulness that may be impacted by adolescent alcohol exposure. The current study investigated the impact of adolescent ethanol exposure on adult orexin-A/hypocretin-1 immunoreactive (orexin-A+IR) cells in hypothalamic nuclei in two models of adolescent intermittent ethanol (AIE) exposure. Both models assess adult hypothalamic orexin following either an AIE vapor exposure paradigm, or an AIE intragastric gavage paradigm during adolescence. Both AIE exposure models found that binge levels of ethanol intoxication during adolescence significantly increased adult orexin-A+IR expression in the anterior hypothalamic nucleus (AHN). Further, both AIE models found no change in orexin-A+IR in posterior hypothalamic area (PH), perifornical nucleus (PeF), dorsomedial hypothalamic nucleus, dorsal (DMD) or lateral hypothalamic area (LH). However, AIE vapor exposure reduced orexin-A+IR in the paraventricular nucleus (PVN), but not AIE gavage exposure. These findings suggest AHN orexinergic system is increased in adults following binge-like patterns of intoxication during adolescence. Altered adult AHN orexin could contribute to long-lasting changes in sleep.